Customs and Duty: Indigenous Hip Hop and the US–Canada Border. Issue 3 (3rd July 2018) - Przybylski, Liz
ABSTRACT: The production of Indigenous hip hop on both sides of the 49th parallel reveals a cultural complexity far beyond a stereotypical melting pot to the south and mosaic to the north. This article demonstrates multiple similarities in Canadian and USAmerican Indigenous hip hop through a parallel analysis of recent music videos by Canadian Cree and Saulteaux rapper Drezus and USAmerican Lakota rapper Frank Waln. Like earlier hip hop that inspires it, Indigenous hip hop on both sides of the border uses place as a central part of its messaging. These videos, with parallel visual narratives, demonstrate how place-based meanings are expressed around the borderlands through the fusion of traditional music into rap music. Building from hip hop scholarship on racially-coded evocations of place, this article argues that referencing place entails more than naming geographies. I analyze three overlapping functions of place: establishing a sense of connection between artist and land, conveying a specific type of authenticity, and forging intergenerational connections. Together, these underline the ongoing relevance of transnational exchange, particularly as relevant to Indigenous popular music. Place in these two contexts offers an anchoring function, yet continues to demonstrate a fluidity upon which artists draw for their music videos. Disparate political possibilities and social realities affect the ways that artists mark connections to land, community, and culture. The way place functions across the border explains how music videos are shaping public discourses around land rights, environmentalism, and global Indigeneity within and across the borders of the US and Canada.